ANALISIS WACANA KRITIS PEMBERITAAN ISU PERCEPATAN REFORMASI KEPOLISIAN PADA MEDIA ONLINE KOMPAS.COM: KAJIAN TEUN A. VAN DIJK - Nainggolan, Indanian; Kurnia Pulungan, Hendra; Khairani, Ita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Online media not only conveys information, but also actively frames reality according to certain ideological interests, including in reporting the issue of accelerating police reform which has recently become a public spotlight. This study aims to analyze the discourse construction of the issue of accelerating police reform in Kompas.com news through text structure (macrostructure, superstructure, microstructure) and the social context behind it, using Teun A. Van Dijk's Critical Discourse Analysis model. This study uses a descriptive qualitative approach with data in the form of ten Kompas.com news texts published from November 7, 2025 to February 25, 2026, analyzed through the interactive model of Miles and Huberman. The results show that Kompas.com constructs police reform as a top-down institutional program through a layered legitimacy pattern: the macrostructure emphasizes formal-procedural legitimacy while eliminating the voices of victims, the superstructure places criticism at the end of the text as a de-escalation strategy, and the microstructure utilizes administrative euphemisms and elite-based authorization. From a social context perspective, a pattern of event substitution was found that dissolves concrete issues into abstract discourse, weakening the accountability pathway and revealing a gap between the media's image of reform and the reality of recurring police issues.